Effects of venetoclax, a BCL2 inhibitor, in systemic chronic active Epstein-Barr virus disease - Ayaka Ohashi; Miwako Nishio; Mayumi Yoshimori; Kaoru Koike; Morito Kurata; Hayato Tamai; Ken-Ichi Imadome; Ayako Arai (Scientific Reports, 2025)
Abstract Systemic chronic active Epstein-Barr virus disease (sCAEBV) is a chemotherapy-resistant, EBV-positive T- or NK-cell lymphoproliferative disorder characterized by persistent systemic inflammation driven by the activation of EBV-infected cells. In this study, we explored BCL2, an anti-apoptotic factor implicated in various hematopoietic malignancies, as a potential therapeutic target for sCAEBV, focusing on the effects of its inhibitor, venetoclax. We confirmed BCL2 expression in EBV-positive T- and NK-cell lines and peripheral blood mononuclear cells (PBMCs) from sCAEBV patients using western blotting. Immunofluorescence staining further revealed BCL2 expression in EBV-infected cells within patient-derived PBMCs. Venetoclax treatment reduced the viability of EBV-positive cell lines and patient-derived PBMCs in a dose-dependent manner and induced apoptosis in these cells. Moreover, venetoclax suppressed the mRNA expression of the inflammatory cytokine IFN-γ in patient-derived PBMCs. To evaluate the in vivo effects of venetoclax, we utilized sCAEBV xenograft model generated by transplanting patient-derived PBMCs into NOD/Shi-scid/IL-2Rγnull mice. No engraftment of EBV-infected cells was observed in mice treated with venetoclax, whereas one out of three mice in the untreated group exhibited engraftment of EBV-positive cells and tumor formation. Venetoclax treatment showed an insignificant trend to reducing IFN-γ levels in peripheral blood in established xenograft models. To our knowledge, this is the first report to suggest that venetoclax exerts not only anti-tumor effects but also potential anti-inflammatory effects in sCAEBV. BCL2 represents a promising therapeutic target to address the two pathological characteristics of sCAEBV: malignancy and inflammation.